2010
DOI: 10.1113/jphysiol.2010.186999
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in GABAAreceptor subunits associated with genetic epilepsies

Abstract: Mutations in inhibitory GABA A receptor subunit genes (GABRA1, GABRB3, GABRG2 and GABRD) have been associated with genetic epilepsy syndromes including childhood absence epilepsy (CAE), juvenile myoclonic epilepsy (JME), pure febrile seizures (FS), generalized epilepsy with febrile seizures plus (GEFS+), and Dravet syndrome (DS)/severe myoclonic epilepsy in infancy (SMEI). These mutations are found in both translated and untranslated gene regions and have been shown to affect the GABA A receptors by altering r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
210
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 245 publications
(217 citation statements)
references
References 53 publications
5
210
0
2
Order By: Relevance
“…In fact, mutations of GABRG2, either missense or truncating, cause a spectrum of seizure disorders, ranging from early-onset isolated febrile seizures to GEFSP, type 3, which represents the most severe phenotype. [29][30][31] The type of febrile seizures present in this patient and in her father fits well with the milder phenotype. The heterozygous mutation of RELN has not been considered as causal of her phenotype because only recessive mutations of this gene are associated with a pathogenic condition characterized by lissencephaly 32 not present in our patient who has a normal psychomotor development.…”
Section: Discussionmentioning
confidence: 66%
“…In fact, mutations of GABRG2, either missense or truncating, cause a spectrum of seizure disorders, ranging from early-onset isolated febrile seizures to GEFSP, type 3, which represents the most severe phenotype. [29][30][31] The type of febrile seizures present in this patient and in her father fits well with the milder phenotype. The heterozygous mutation of RELN has not been considered as causal of her phenotype because only recessive mutations of this gene are associated with a pathogenic condition characterized by lissencephaly 32 not present in our patient who has a normal psychomotor development.…”
Section: Discussionmentioning
confidence: 66%
“…Surprisingly, such a functional outcome did not require the activation of extrasynaptic GABA A receptors. We further demonstrated that the down-regulation of phasic inhibition is not due to the positional effect of ␣6␤3␦ receptors because inserting a gephyrin-binding site (GBS) 3 into the ␣6 and ␦ subunits targeted ␣6 GBS ␤3␦ GBS receptors to postsynaptic sites but could not rescue phasic inhibition. Interestingly, overexpressing ␣5␤3␥2-receptors also decreased synaptic GABAergic transmission.…”
mentioning
confidence: 98%
“…Our recent work revealed that, in addition to ␥2 and ␦ subunits, ␣ subunits also play a direct role in targeting GABA A receptors to synaptic and extrasynaptic sites (2). Dysfunction of both synaptic and extrasynaptic GABA A receptors has been associated with neurological disorders such as anxiety, depression, and epilepsy (1,(3)(4)(5). Because synaptic and extrasynaptic GABA A receptors have distinct spatial localization and mediate distinct temporal inhibition, it is unclear how synaptic and extrasynaptic GABA A receptors may interact with each other to regulate the total inhibition.…”
mentioning
confidence: 99%
“…In their latest publication, Kang and coworkers further unravel some of the complexity underlying this deceptively simple concept by examining mutations in the GABA A receptor γ 2 subunit (GABA A receptors typically consist of two α 1 , two β 2 and one γ 2 subunits) (3). Mutations in the γ 2 subunit have been linked to syndromes across the spectrum of the epilepsies, from benign childhood absence epilepsy to the very serious Dravet syndrome (4).…”
Section: Commentarymentioning
confidence: 99%